The VOILA Instrument: Laser-Induced Breakdown Spectroscopy at the Lunar South Pole - Vogt, David; Schröder, Susanne; Hübers, Heinz-Wilhelm; Richter, Lutz; Deiml, Michael; Wessels, Peter; Neumann, Jörg (2021)
Water at the lunar south pole is of great interest for upcoming lunar exploration endeavors. Here, we present the VOILA instrument that is capable of detecting hydrogen with laser-induced breakdown spectroscopy (LIBS). It is also capable of detecting all major rock-forming elements, enabling the detailed analysis of the lunar regolith as well as the detection of water.